Wet SPF: A wet powder suspension for the detection of latent fingermarks on the sticky side of adhesive tape for use in Seychelles - Bouzin, Jemmy T.; Sauzier, Georgina; Lewis, Simon (2024)
WET UCIO is an inexpensive carbon-based powder suspension, reportedly as effective as commercially available formulations for latent fingermark detection on the sticky side of adhesive tapes. However, the surfactant solution used in WET UCIO is not readily accessible outside Europe, limiting its use in Seychelles or other non-European jurisdictions. In this study, the UCIO formulation was modified based on a ‘frugal forensic’ approach, by replacing the surfactant solution with an in-house sodium dodecyl sulfate solution prepared in 5% aqueous ethanol. A comparative assessment against Wetwop™ using eight different pressure-sensitive adhesive tapes found that the modified formulation was at least as effective as commercial powder suspension. Modifying this technique under the frugal forensic framework has enhanced its accessibility to other jurisdictions and is recommended for validation in Seychelles.